The influence of diabetes mellitus and insulin therapy on biomechanical retention around dental implants: a study in rabbits. - Margonar, Rogério; Sakakura, Celso E; Holzhausen, Marinella; Pepato, Maria Teresa; Alba, júnior Rodolfo Cândia; Marcantonio, júnior Elcio (My University, 2003)
The oral rehabilitation by dental implants in patients with diabetes remains a controversial issue. The aim of this study was to evaluate the influence of diabetes mellitus and insulin therapy on the bone healing around dental implants using torque removal. Twenty-seven rabbits were randomly divided into 3 groups with 9 animals each: control (C) group, induced diabetic (D) group, and insulin-treated diabetic (ITD) group (10 U/day). After 1 week, one implant was inserted at the tibial metaphysis of the animals. The glucose levels were periodically evaluated through the glucose-oxidase enzymatic method. The animals were killed at 4, 8, and 12 weeks after surgery and the biomechanical test was performed using a torque manometer. Statistically significant differences regarding the removal torque of the implant could not be found at 4 weeks (P = 0.2) among groups. Group C showed statistically higher values than groups D and ITD at the experimental periods of 8 (P = 0.0001 and P = 0.0002, respectively) and 12 weeks (P = 0.0053 and P = 0.001, respectively). There were no statistical differences between D and ITD groups in any of the experimental periods. Diabetes mellitus has negatively influenced the mechanical retention of implants placed at the tibial metaphysis of rabbits. Therapy with insulin did not induce any changes.
Keywords: insulin; analysis of variance; animal; biomechanics; bone regeneration; device removal; experimental diabetes mellitus; female; implant; nonparametric test; pathophysiology; rabbit; tibia; time; tooth implantation; torque; Analysis of Variance; Animals; Biomechanics; Dental Implantation, Endosseous; Dental Implants; Device Removal; Diabetes Mellitus, Experimental; Female; Implants, Experimental; Insulin; Osseointegration; Rabbits; Statistics, Nonparametric; Tibia; Time Factors; Torque